2016
DOI: 10.1093/annonc/mdw261
|View full text |Cite
|
Sign up to set email alerts
|

Outcome according to KRAS-, NRAS- and BRAF-mutation as well as KRAS mutation variants: pooled analysis of five randomized trials in metastatic colorectal cancer by the AIO colorectal cancer study group

Abstract: In this pooled analysis of metastatic colorectal cancer patients, mutations in KRAS, and BRAF were associated with inferior progression-free and overall survival compared with patients with non-mutated tumors. KRAS exon 2 mutation variants were associated with heterogeneous outcome compared with unmutated tumors with KRAS G12C and G13D being associated with rather poor survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
176
3
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(207 citation statements)
references
References 31 publications
23
176
3
5
Order By: Relevance
“…The frequency of KRAS mutations (33.3%) and BRAF mutations (2.3%) in the present study were in accordance with a previous retrospective observational study that also involved Chinese patients with mCRC (34.8 and 3.4%, respectively) (20). However, the KRAS and BRAF mutation rate was slightly higher in the Western population (37.3 and 6%) (10). Since the morbidity and mortality of CRC in China were different from that in Western countries, the KRAS and BRAF mutation rates in different regions required further exploration (21).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The frequency of KRAS mutations (33.3%) and BRAF mutations (2.3%) in the present study were in accordance with a previous retrospective observational study that also involved Chinese patients with mCRC (34.8 and 3.4%, respectively) (20). However, the KRAS and BRAF mutation rate was slightly higher in the Western population (37.3 and 6%) (10). Since the morbidity and mortality of CRC in China were different from that in Western countries, the KRAS and BRAF mutation rates in different regions required further exploration (21).…”
Section: Discussionsupporting
confidence: 91%
“…This result was consistent with the evidence from in vitro studies, in which codon 12 mutations may increase aggressiveness due to increased transforming capacity and decreased levels of apoptosis (16,30). Previously, meta-analysis also revealed the predictive value that codon 12 mutations possessed by pooling the data from five randomized trials researching patients with mCRC in Western countries (10). In that meta-analysis, G12C was associated with inferior OS compared with KRAS wild-type; however, the results of the present study demonstrated that G12D and G12V were associated with decreased OS times.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…KRAS mutations were found in 50.87% of our patients, which is higher than in previous reports from other countries [49,50] . In the current study, KRAS mutations showed no significant difference between males and females, although some studies reported increased frequency among males [50] , and other reports demonstrated different patterns of KRAS mutations in men and women [49,50] . Our findings not only supported the well-established role of KRAS mutation in predicting resistance to the EGFR-blocking antibody cetuximab, but also highlighted the role of KRAS mutation as a predictive marker of poor prognosis and inferior patient survival.…”
Section: Discussioncontrasting
confidence: 74%